Traditional styles of artistic and industrial art in global practices - Dyachenko, Alla (Art and Design, 2026)
Despite the growing interest in arts and crafts, there is no systematic typology of its stylistic and technological characteristics that would be used to integrate local traditions into the global artistic discourse. The study aimed to analyse key trends and identify leading authorial techniques and traditional styles in 21 st - century industrial art, using the creative practices of contemporary foreign artists as examples. The study used comparative, historical-cultural, content and discourse analysis. The main results of the study showed that industrial art is under the powerful influence of globalisation processes and technological transformations, but at the same time is increasingly returning to craft traditions. The study revealed that master craftsmen, working in an open transcultural space, reinterpret traditional styles not as archaic or outdated forms, but as a means of forming new cultural codes. Traditional craft techniques and materials are acquiring the status of conceptual tools capable of conveying complex meanings, deep-rooted identities and historical memory. At the same time, technological innovations (digital media, automated production, 3D printing, etc.) contribute to the formation of new formats of creativity that combine aesthetics, functionality and sustainability. The factors that shape contemporary aesthetic guidelines, sociocultural strategies and craft practices in a transcultural environment have been summarised and systematised. The analysis of the effect of combining innovative technologies and traditional techniques on the emergence of new artistic languages and models of interaction between art and society was emphasised. The study proved that the combination of authorial techniques and craft approaches with modern technologies creates the basis for the renewal of artistic and industrial art and the formation of its competitiveness on the world stage. The results can be used to develop concepts for integrating traditional stylistics into contemporary artistic practices, which is particularly relevant in the processes of preserving cultural identity